Evaluation of Intestinal Parasite Infection in Low and High Coverage of Graduated Households, Northwest Ethiopia: A Comparative-Based Crosssectional Study - Desalegn Andargie; Yalewayker Tegegne; Ligabaw Worku (Journal of Parasitology Research)
Intestinal parasite infections are widely distributed and affect various segments of the population in Ethiopia as in many developing countries. The government launched an innovative program called Health Extension Program to increase the coverage of primary health care services, mainly by producing model households using model-family training. The aim of this study was to evaluate the intestinal parasite infection in low and high coverage of graduated households. Method. A community-based crosssectional study was conducted from February to June, 2019. A total of 478 participants were enrolled in this study by using a multistage sampling technique. Data were collected by using pretested and semistructured questionnaire. Five grams of stool specimen was collected, and samples were processed using a direct wet mount and Kato Katz technique. Data were coded, entered, and cleaned using statistical package for social science (SPSS) version 20. A Chi-square test was employed to compare the two groups. P value < 0.05 were taken as statistically significant. Result. The prevalence rate of IPIs was 39% and 20.5% in LCGHH and HCGHH, respectively. A. lumbricoides was the predominant parasite, detected in 14.6% and 8.8% followed by S. mansoni 6.3% and 2.1% in LCGHH and HCGHH districts, respectively. LCGHH had significantly higher prevalence of A. lumbricoides, S. mansoni, and hookworm infections than the HCGHH district (P<0.05). Thirteen (18.8%) study participants in LCGHH and four (11.7%) in HCGHH showed heavy infection with the four common soil-transmitted helminths (A. lumbricoides, S. mansoni, hookworm, and T. trichiura). Among study participants who were positive for S. mansoni, 53.3% in LCGHH and 20% in HCGHH had heavy infection for the Kato thick smear used. Conclusion. The prevalence of IPIs is significantly higher in LCGHH than in the HCGHH district. Producing more model households by giving model family training to nonmodel households and strengthening the information, education, and communication package are crucial in the implementation of the HEP to decrease the prevalence of IPIs especially in LCGHH districts.